PENGARUH KOPIGMENTASI TERHADAP STABILITAS WARNA ANTOSIANIN EKSTRAK KULIT TERUNG BELANDA (Cyphomandra betacea Sendtn) [Copigmentation Effect on Color Stability of Anthocyanin from Epicarp Extract of Terung Belanda (Cyphomandra betacea Sendtn)] - Herlina Wahyuni; Tirza Hanum; Murhadi Murhadi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2017)
Copigmentation has been suggested as a main color stabilizing mechanism of the anthocyanin. The objectives of this research were to determine type and molar ratio of copigment (catechol or tannin) to anthocyanin which most stabilize the color of anthocyanin from epicarp extract of Terung Belanda (Cyphomandra betacea Sendtn) during 40 days storage. Stability of anthocyanin was evaluated from changes of anthocyanin concentration and color retention during storage period and kinetic parameters. The initial anthocyanin content from epicarp extract of Terung Belanda (Cyphomandra betacea Sendtn) was 0,31 mMol/L (0,20 mg/100g). Copigmentation with catecholwas less effectiveto stabilizethe color of anthocyanin, indicated by the concentrationof anthocyaninsat molar ratio 0:1, 50:1 and 100:1 which was not significantly different. Meanwhile, the color retentionat pH 3,5 and kinetic reaction of antocianin at 65oC with molar ratio 50:1 stabilized the anthocyanin extract of epicrap Terung Belanda (Cyphomandra betacea Sendtn) (color retention 44,35%, k 0,141 and t½ 4,91 hours). Copigmentation with tannin at molar ratio 100:1 was more effectiveto stabilize the color of anthocyanin indicated by decreasing of concentration of anthocyanins and color retention at pH3,5 after 40 days storage which were 0,10 mMol/L (69,70%) and 63,56%. Kinetics parameter at 65oC(k) 0,063 and t½ 11,00 hours.Keywords: anthocyanin, catechol, copigmentation, Cyphomandra betacea Sendtn, tannin.